Advanced Strategies for Modulation of the Material–Macrophage Interface. (3rd April 2020) - Davenport Huyer, Locke; Pascual‐Gil, Simon; Wang, Yufeng; Mandla, Serena; Yee, Bess; Radisic, Milica
Abstract: Biomaterials are becoming increasingly crucial for healthcare solutions, with extensive use in the field of tissue engineering and drug delivery. After implantation, biomaterials trigger an immune response characterized by the recruitment of bone‐marrow‐derived proinflammatory macrophages that develop as the most abundant cell type surrounding the biomaterial. Chronic activation of this recruited macrophage population induces a foreign body reaction response and consequent biomaterial rejection. However, transition toward a proreparative phenotype is associated with biomaterial integration and tissue homeostasis restoration. In this review, the most relevant strategies that modulate biomaterial immune response are discussed, including mechanical properties, surface coatings, release of anti‐inflammatory molecules and cytokines, antibacterial features, origin and inner moieties of biomaterials, and cell crosstalk. Moreover, the role of tissue resident macrophages, an embryo‐derived macrophage population with a strong reparative potential, in promoting biomaterial tolerance will be reviewed. This provides new insights to better tune the reaction of the host immune system to implanted biomaterials in order to favor integration and increase the knowledge of macrophages as key players in tissue homeostasis. Abstract : Macrophages are drivers of the cellular response to implanted material constructs. This review discusses the important considerations in macrophage interactions with biomaterials and summarizes progress in material design to optimize implant outcomes. Opportunities to broaden design criteria to consider the tissue resident macrophage population in future innovations are highlighted.